2019
DOI: 10.1136/vr.104944
|View full text |Cite
|
Sign up to set email alerts
|

Canine dystocia in 50 UK first‐opinion emergency care veterinary practices: clinical management and outcomes

Abstract: Canine dystocia is a relatively common veterinary presentation. First opinion emergency care clinical data from 50 Vets Now clinics across the UK were used to explore dystocia management and outcomes in bitches. Caesarean section (CS) was performed on 341/701 (48.6 per cent (95 per cent CI 44.9 to 52.4)) of dystocia cases. The bulldog (OR 7.60, 95 per cent CI 1.51 to 38.26, P=0.014), Border terrier (OR 4.89, 95 per cent CI 0.92 to 25.97, P=0.063) and golden retriever (OR 4.07, 95 per cent CI 0.97 to 17.07, P=0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 30 publications
1
35
0
Order By: Relevance
“…Script theory proposes a rationale for how clinicians store sets of pre-compiled knowledge called ‘illness scripts’ as mental models of real-world disorders; these illness scripts then influence the probability of certain diagnoses being reached 51 . Since illness scripts depend heavily on prior knowledge and beliefs, it stands to reason that increasing awareness of heightened risk of certain disorders such as corneal ulceration 12 or dystocia 13 , 14 in brachycephalic breeds will bias the probability of such diagnoses in these breeds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Script theory proposes a rationale for how clinicians store sets of pre-compiled knowledge called ‘illness scripts’ as mental models of real-world disorders; these illness scripts then influence the probability of certain diagnoses being reached 51 . Since illness scripts depend heavily on prior knowledge and beliefs, it stands to reason that increasing awareness of heightened risk of certain disorders such as corneal ulceration 12 or dystocia 13 , 14 in brachycephalic breeds will bias the probability of such diagnoses in these breeds.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some veterinarians now consider the health and welfare of several popular brachycephalic breeds too compromised to justify their continued breeding 8 . A growing body of evidence is accumulating to suggest that brachycephalic breeds are strongly predisposed to a range of disorders intrinsically related to their typical conformations, including respiratory disease 9 , 10 , eye disease 11 , 12 , dystocia 13 , 14 , spinal disease 15 , heat stroke and pneumonia 16 . Brachycephalic breeds are also reported with significantly shorter lifespans (median longevity: 8.6 years) than moderate and non-brachycephalic dogs (median 12.7 years) 17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary-care veterinary clinical data are now recognised as a valuable research resource that benefit from contemporaneous recording of medical records at the time of the clinical event, and from the recording of cohort data over time and at a veterinary level of clinical precision [27,28]. Such data have been validated for research purposes by several previous reports on diverse conditions in dogs including road traffic accidents [29], appendicular osteoarthritis [30], dystocia [31], urinary incontinence [32], and corneal ulcerative disease [33]. The current study aimed to fill the information gap on the epidemiology of elbow joint disease by estimating the prevalence and incidence of elbow joint disease in dogs attending primary-care veterinary practice in the UK and evaluating breed as a risk factor for incident elbow joint disease.…”
Section: Introductionmentioning
confidence: 99%
“…Also priortised at the 3rd IDHW was movement towards open access publication to encourage wider disemination of research findings and there is some evidence that research papers are increasingly likely to be published as open access since then [37,53,54]. There has also been evidence of increased research output on two key areas identified as priorities at the 3rd IDHW 2017: disease prevalence/incidence, risk factors, and geographic spread [53,[55][56][57][58] and also quality-of-life and end-of-life data [59,60].…”
Section: Ipfd Harmonization Of Genetic Testing For Dogs: An Internatimentioning
confidence: 99%